A mating-induced reproductive gene promotes Anopheles tolerance to Plasmodium falciparum infection - Marcenac, Perrine; Shaw, W. Robert; Kakani, Evdoxia G. (PLoS Pathog, 2020)
Anopheles mosquitoes have transmitted Plasmodium parasites for millions of years, yet it remains unclear whether they suffer fitness costs to infection. Here we report that the fecundity of virgin and mated females of two important vectors—Anopheles gambiae and Anopheles stephensi—is not affected by infection with Plasmodium falciparum, demonstrating that these human malaria parasites do not inflict this reproductive cost on their natural mosquito hosts. Additionally, parasite development is not impacted by mating status. However, in field studies using different P. falciparum isolates in Anopheles coluzzii, we find that MatingInduced Stimulator of Oogenesis (MISO), a female reproductive gene strongly induced after mating by the sexual transfer of the steroid hormone 20-hydroxyecdysone (20E), protects females from incurring fecundity costs to infection. MISO-silenced females produce fewer eggs as they become increasingly infected with P. falciparum, while parasite development is not impacted by this gene silencing. Interestingly, previous work had shown that sexual transfer of 20E has specifically evolved in Cellia species of the Anopheles genus, driving the co-adaptation of MISO. Our data therefore suggest that evolution of male-female sexual interactions may have promoted Anopheles tolerance to P. falciparum infection in the Cellia subgenus, which comprises the most important malaria vectors.
Keywords: Anopheles gambiae; eggs; mosquitoes; Sara N. Mitchell; Adam South; CEA-ITECH_MTV; ACE: Bio-technological Innovation for the Elimination of Vector- Borne Diseases; Université Nazi Boni; Burkina Faso